The Path of Poetic Knowledge of Maria Zambrano (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This article aims to present the work of the Spanish philosopher Maria Zambrano (1904-1991). Her name and work were enshrouded in silence in Spain itself until the last decades of the 20th century. Zambrano cultivated a large part of her intellectual activities in exile during the Spanish Civil War. After returning to Spain almost half a century later, in 1988, she received the highest national recognition for literature, the Cervantes Prize. Anthropological existentialism, political and social engagement and Spain’s fate are some of the main topics on which Zambrano reflects in different ways in her numerous published books. The scope of her thought, which follows many postulates of Spinoza’s ethics, is now finally available in the first complete edition of Maria Zambrano’s collected works in Spanish, which opens the possibility of a systematic approach to certainly one of the greatest figures of Spanish philosophy.
Keywords: Maria Zambrano; Spanish philosophy; women philosophers; Republican Spain; poetic reason